Electrical controllable spin pump based on a zigzag silicene nanoribbon junction. (16th November 2017) - Zhang, Lin; Tong, Peiqing
Abstract: We propose a possible electrical controllable spin pump based on a zigzag silicene nanoribbon ferromagnetic junction by applying two time-dependent perpendicular electric fields. By using the Keldysh Green's function method, we derive the analytic expression of the spin-resolved current at the adiabatic approximation and demonstrate that two asymmetric spin up and spin down currents can be pumped out in the device without an external bias. The pumped currents mainly come from the interplay between the photon-assisted spin pump effect and the electrically-modulated energy band structure of the tunneling junction. The spin valve phenomena are not only related to the energy gap opened by two perpendicular staggered potentials, but also dependent on the system parameters such as the pumping frequency, the pumping phase difference, the spin–orbit coupling and the Fermi level, which can be tuned by the electrical methods. The proposed device can also be used to produce a pure spin current and a 100% polarized spin current through the photon-assisted pumping process. Our investigations may provide an electrical manipulation of spin-polarized electrons in graphene-like pumping devices.